Psychometric properties of the Impact Index in patients with chronic conditions - KD Valentine; Suzanne Brodney; Carol Cosenza; J. Hargraves; Karen Sepucha; Susan Edgman-Levitan; Michael Barry (The Beryl Institute, 2023)
The purpose of this paper was to extend the generalizability of the patient-reported Impact Index by assessing convergent validity in patients with common chronic conditions. We conducted a cross-sectional survey of 1,000 English-speaking patients aged 21 and older who visited their provider in the past 6 months and were included in one or more of a hospital's chronic condition registries. Patients completed a survey that included the Impact Index (4-item measure of how impacted a patient is by their health condition: range 0-12, higher score indicating greater negative impact on quality of life), overall health, and self-report of diagnosis of 8 chronic conditions. Patients were categorized as having symptomatic conditions (one or more symptomatic conditions) or asymptomatic conditions. We hypothesized that Impact Index scores would be negatively correlated with overall health, positively correlated with the number of chronic conditions (using Pearson correlations) and would be higher for symptomatic than asymptomatic conditions (using an independent t-test). Of the 492 respondents (50% response rate), 381/392 eligible respondents completed all Impact Index items. Impact Index scores ranged from 0 to 12 (M=6, SD=4). As reports of overall health increased (i.e., from poor to excellent), Impact Index scores decreased (r=-0.59, p<.001). As the number of chronic conditions increased, so did Impact Index scores (r=0.33, p<.001). Patients with symptomatic conditions reported higher Impact Index scores (M=6.6, SD=3.5) than those with asymptomatic conditions (M=4.1, SD=3.5, p<.001, d=.70). These findings support the validity of the Impact Index for patients with a range of chronic conditions. Experience Framework This article is associated with the Policy & Measurement lens of The Beryl Institute Experience Framework (https://theberylinstitute.org/experience-framework/). Access other PXJ articles related to this lens. Access other resources related to this lens.